2015
DOI: 10.1002/chin.201528329
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Atmospheric Pressure Anion Mass Spectrometry: Electron Affinities and Activation Energies of Thermal Electron Attachment — Perfluoromethylcyclohexane, C7F14

Abstract: Review: 51 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The ionization energy of hexacene in the NIST database 6.36 (2) eV and that of naphtho[1,2‐b]triphenylene 7.40 (2) eV give AE a = EN‐IE of 8.00 − 6.36 = 1.64 eV and 8.00 − 7.40 = 0.60 eV, in agreement with the reported AE a values of 1.58 (5) eV and 0.61 (3) eV from half‐wave reduction potentials . Finally, it is suggested that, assuming that thermal decomposition does not take place, the ground state AE a of hexacene and pentacene could be measured from high‐temperature mass spectrometric thermal data as applied to SF 6 and C 7 F 14 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The ionization energy of hexacene in the NIST database 6.36 (2) eV and that of naphtho[1,2‐b]triphenylene 7.40 (2) eV give AE a = EN‐IE of 8.00 − 6.36 = 1.64 eV and 8.00 − 7.40 = 0.60 eV, in agreement with the reported AE a values of 1.58 (5) eV and 0.61 (3) eV from half‐wave reduction potentials . Finally, it is suggested that, assuming that thermal decomposition does not take place, the ground state AE a of hexacene and pentacene could be measured from high‐temperature mass spectrometric thermal data as applied to SF 6 and C 7 F 14 …”
Section: Discussionsupporting
confidence: 80%
“…In 2004, the electron affinities in the NIST database were reviewed . Since 2004, several negative ion mass spectrometric studies have been carried out on AHC or other compounds so it is pertinent to revisit the ECD data . This communication provides ground state AE a from ECD or other data for the 15 compounds listed in Table , to be used for comparison with mass spectrometric data.…”
Section: Introductionmentioning
confidence: 99%